(untitled) (Praxis Educativa, 2023)
Initial teacher education is one of the most relevant areas of educational research given its impact on the processes of design and implementation of public policies related to education overall. In methodological terms, the design of this research includes qualitative techniques, among which the normative legal analysis and the consequent generation of comparative typification of the sources considered stand out. Data collection was carried out through various strategies, which included a survey of normative documents (educational legislation, resolutions, regulations, curricular designs) at the national and subnational levels and also from the university institutions referring to teacher education and/or to the dimensions considered. Definitions related to initial teacher education for the primary school (from an international comparative perspective), federalism, and its implications in terms of curricula, in light of the reform processes, are discussed. It is noted that, although Argentina has had a profuse normative regulation in this area, the results of the reforms have not led to a comprehensive teacher education policy. This is due both to the federal form of the Argentine State (and the autonomy of the provinces) and to the binary nature of higher education (with the particularity of the autonomy of the national universities).